2011
DOI: 10.1007/s00204-011-0703-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of spontaneous cell death in monolayer cultures of primary hepatocytes

Abstract: Monolayer cultures of primary hepatocytes, isolated from freshly removed livers, represent widely used in vitro tools in the area of liver physiology and pathology, pharmacology and toxicology. However, a major shortcoming of these systems is that they cope with dedifferentiation, which is accompanied by spontaneous cell death. The goal of the present study was to elucidate the mechanisms that drive the process of self-generated cell demise in primary hepatocyte cultures. For this purpose, isolated rat hepatoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…We were not able to consistently observe a decrease of UA cytotoxicity in hepatocytes pre‐treated with CYP inducers for 24 h, although the cytotoxicity of leflunomide was significantly decreased using a 24‐h pre‐treatment with CYP inducers, as reported (Shi et al ., ). It has been well recognized that monolayer cultures of primary hepatocytes tend to lose many normal phenotypes 24 h after isolation (Vinken et al ., ). This might be the reason that hepatocytes treated with CYP inducers for 24 h did not respond to UA challenge as expected.…”
Section: Discussionmentioning
confidence: 97%
“…We were not able to consistently observe a decrease of UA cytotoxicity in hepatocytes pre‐treated with CYP inducers for 24 h, although the cytotoxicity of leflunomide was significantly decreased using a 24‐h pre‐treatment with CYP inducers, as reported (Shi et al ., ). It has been well recognized that monolayer cultures of primary hepatocytes tend to lose many normal phenotypes 24 h after isolation (Vinken et al ., ). This might be the reason that hepatocytes treated with CYP inducers for 24 h did not respond to UA challenge as expected.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, hepatocytes appear to show less spreading when cultured in the presence of serum and on substrates other than collagen (Vinken et al. ; Godoy et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…35) Noy and colleagues also indicated that knockdown of Hex gene increased cell proliferation, and the increase was enhanced by stimulation with VEGF in K562 cells. 32) However, the precise molecular mechanism and the executioner of the cell death by Hex were not described in the report.…”
Section: /Pimentioning
confidence: 98%